The Effect of Powder Detergent Water on Shrinkage Cracks of Soil Due to Drying. (11th June 2022) - Zhang, Shaowei; Li, Dongdong
Abstract : In this study, the effect of powdered detergent content in grey water on the evaporation and cracking characteristics of soils used in agricultural irrigation was investigated. Soil samples treated with different concentrations of detergent solutions (mass of powder detergent to soil mass of 0, 0.2%, 0.4%, 0.8%, 1.6%, and 3.2%) were used in laboratory evaporation testing to obtain the variation water content and cracking images during the evaporation process. Through image processing technology, the crack ratio and fractal dimensions of the cracks were used as evaluation indexes to quantitatively analyze the crack development of samples during the evaporation process. The results show that the water content of the soil samples treated with the detergent solution slightly increases compared to the control soil sample with no detergent. The maximum difference in water content between the samples with and without 0.8% detergent is 7.8%. The total time of the appearance of initial cracks of soil samples treated with detergent was shorter at a higher water content. The final crack ratio and fractal dimensions of the samples treated with different detergent solutions were all larger than the control sample. The soil samples with 1.6% and 3.2% detergent have precipitation of the grains during the evaporation process and form a flocculent layer on the surface of the sample. The dispersion of the soil samples was enhanced significantly after testing. The purpose of this study is to provide some valuable insights into application and management of grey water irrigation in arid and semi-arid areas.